Five Easy Steps to Preparing Effective Reasons for Dairy Cattle Judging Contests II. - Russ Giesy; James Umphrey (EDIS)
This document is 4HDAJ02 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published in May, 1997; reviewed June 2002.